Academic Freedom and the Onset of Autocratization - Pelke, Lars (Democratization, 2023)

Academic Freedom Growth and Decline Episodes - Lott, Lars (Higher Education, 2024)

Academic Freedom Index 2022 Update - Kinzelbach, Katrin; Lindberg, Staffan I.; Pelke, Lars; Spannagel, Janika (2022)

Academic Freedom Index 2024 Update - Kinzelbach, Katrin; Lindberg, Staffan I.; Lott, Lars (2024)
The latest edition of the Academic Freedom Index (AFI) provides an overview of the state of academic freedom in 179 countries in 2023, and trends over time. The AFI assesses de facto levels of academic freedom and is a unique and peer-reviewed approach to conceptualizing and assessing academic freedom worldwide.1 The aggregate index rests on five indicators, a customized Bayesian measurement model, and more than one million data points at the coder level.2 It builds on the expertise of 2,329 scholars around the globe and is freely available at https://academic-freedom-index.net and https://www.v-dem.net. The findings presented in this year’s update build upon the AFI team’s research published in several journals in recent years.3 In line with previous AFI reports,4 this year’s data demonstrate that academic freedom globally is under threat. Using the concept of growth and decline episodes at the country level,5 the report shows that 23 countries are in episodes of decline in academic freedom, but that academic freedom is increasing in only ten countries. 3.6 billion people now live in countries where academic freedom is completely restricted. Accounting for a longer timeframe by comparing 2023 data with that of 50 years ago, we note more optimistically that academic freedom has expanded in 56 countries. Figure 1 shows the state of academic freedom in 2023, based on the latest version of the Academic Freedom Index (AFI).<br
Keywords: Academic Freedom Index; academic freedom

Academic Freedom Index 2025 Update - Kinzelbach, Katrin; Lindberg, Staffan I.; Lott, Lars; Panaro, Angelo (2025)

Academic Freedom Index Update 2023 - Kinzelbach, Katrin; Lindberg, Staffan I.; Pelke, Lars; Spannagel, Janika (2023)

Autokratische Redistribution - Institutionen, Legitimation und die Umverteilung von Einkommen in Nicht-Demokratien - Pelke, Lars; Croissant, Aurel (Zeitschrift für Vergleichende Politikwissenschaft, 2018)

Book review of "Property without Rights. Origins and Consequences of the Property Rights Gap", by Michael Albertus. - Pelke, Lars (2022)

Book review of "Varieties of Democracy: Measuring Two Centuries of Political Change", by Michael Coppedge et al - Pelke, Lars (2021)

Book review of "When soldiers rebel", by Kristin A. Harkness - Pelke, Lars (2020)

Conceptualizing and Measuring Autocratization Episodes - Pelke, Lars; Croissant, Aurel (Swiss Political Science Review, 2021)
Autocratization affects democracies and autocracies with gradual setbacks in democratic qualities. The current debate on autocratization is lacking a comprehensive and systematic overview of different autocratization concepts and empirical measures. Addressing the gap, this research note identifies and discusses different strategies of operationalizing autocratization periods with continuous democracy data from Freedom House, Polity IV and the Varieties of Democracy (V-Dem) project. Evidence for 26 different autocratization measures for 1900-2019 reveals major inconsistencies between different measures. Our findings suggest that autocratization episodes should be measured with V-Dem’s Electoral Democracy Index (EDI) or with V-Dem’s Liberal Democracy Index (LDI), which provide fine-grained data and the possibility to test for measurement noise. A 10% threshold reduces the risk of conceptual stretching and enables researchers to detect both autocratization episodes that do and do not result in regime breakdown. We also recommend researchers to additionally test empirical findings with different carefully selected thresholds.
Created from Fastlane, Scopus look-up
Keywords: Autocracy; Autocratization; Democracy; Democratic backsliding; Democratic breakdown

COVID-19 and Democracy: Creeping Autocratization? - Croissant, Aurel; Pelke, Lars (Democracy, State-Capacity and the Governance of COVID-19 in Asia and Oceania, 2023)

Democracy and Development in Asia - Croissant, Aurel; Pelke, Lars; et al. (Research Handbook on Democracy and Development, 2021)

Democratization Articles Dataset: an introduction - Pelke, Lars; Friesen, Paul (Democratization, 2019)

Economic inequality, income, and their effects on electoral and civil society participation in authoritarian regimes - Pelke, Lars (Zeitschrift für Vergleichende Politikwissenschaft, 2020)

Expert:innendaten in der internationalen Menschenrechtsforschung am Beispiel des Academic Freedom Index - Lott, Lars (Zeitschrift für Menschenrechte, 2023)

Inclusionary regimes, party institutionalization and redistribution under authoritarianism - Pelke, Lars (Democratization, 2020)

Index der Wissenschaftsfreiheit - Pelke, Lars (BioSpektrum, 2022)
CRIS-Team Scopus Importer:2022-04-15

Measuring Autocratization - Lott, Lars; Croissant, Aurel (Routledge Handbook of Autocratization, 2024)
This chapter provides a systematic review of the research on measuring autocratization, including its sub-dimensions such as democratic recession and autocratic hardening. We begin by outlining the debate on how to measure democracy, distinguishing between objective and subjective measures. We argue that subjective data should be used to measure autocratization processes, as “more objective” measures of democracy often lack conceptual clarity and theoretical embeddedness. We then differentiate between binary and continuous data on democracy, and illustrate how autocratization can be measured with these two types of data. Additionally, we differentiate between different approaches, namely the delta approach and the episode approach, for embedding change over time to measure autocratization with continuous democracy data. All of these approaches require the use of theoretically informed thresholds to identify autocratization. By providing a comprehensive overview of the literature and outlining a systematic approach for measuring autocratization, this chapter contributes to a better understanding of the process of autocratization and its sub-dimensions.<br

Measuring Policy Performance, Democracy, and Governance Capacities: A conceptual and methodological assessment of the Sustainable Governance Indicators - Croissant, Aurel; Pelke, Lars (European Policy Analysis, 2022)
This paper provides a critical assessment of the Sustainable Governance Indicators (SGI) and compares it with other prominent indices that address specific components of governance: V-Dem, WGI, and BTI. We offer a comparative assessment of content validity of these governance measures, their data generation processes, and their convergent validity. We conclude that the SGI’s most important contribution is the conceptualization of policy performance as a discrete index. Other relative strengths are the theoretical embeddedness and the exclusion of irrelevant meanings of governance, and the conceptualization of three governance components (Governance, Policy Performance, and Democracy). However, in terms of geographic and temporal coverage, the SGI is clearly inferior to WGI and V-Dem. The handling of third-party statistical data, the absence of uncertainty scores, and the (a-theoretical) aggregation of different indicators are additional shortcomings of the SGI. Finally, the SGI’s iterative process of expert deliberation has merits but is prone to biases.
Created from Fastlane, Scopus look-up
Keywords: Democracy; Governance; Policy Performance; Sustainable Governance Indicators (SGI); V-Dem

Party institutionalization, authoritarian regime types and women’s political equality - Pelke, Lars (Contemporary Politics, 2021)
This article examines the association between women’s political inclusion and incumbent party strength in authoritarian regimes. It argues that the degree of party institutionalisation is the main determinant of women’s political inclusion under authoritarian rule. Institutionalised party rule determines the incentive and capacity for authoritarian parties to introduce more gender equal political processes and political outputs. Using different measurements of women’s political inclusion and data on 108 countries between 1946 and 2010, this article estimates within- and between-country effects of party institutionalisation, regime types and political inclusion of women. Although previous research stressed the link between authoritarian regime types and gender equality, this study finds regime types to explain little gender equality variation. In contrast, regimes with higher levels of party institutionalisation provide more gender equal politics and policies than regimes in which authoritarian parties are less institutionalised.
Created from Fastlane, Scopus look-up
Keywords: authoritarian regimes; Gender equality; party institutionalisation; women and politics; women's political inclusion

Quality Assessment of the Academic Freedom Index: Strengths, Weaknesses, and How Best to Use It - Lott, Lars; Spannagel, Janika (Perspectives on Politics, 2025)
This article reviews the data quality of the first systematic global measurement of academic freedom, the Academic Freedom Index (AFI), by using a data quality assessment approach proposed by McMann et al. (2022). By analyzing three distinct components of data quality (content validity, the data generation process, and convergent validity), we examine the specific strengths and potential shortcomings of the AFI. The findings indicate that the AFI does well in terms of its theoretical embeddedness (within some conceptual limits), of the transparent data generation process, and the handling of expert assessments, as well as of its temporal and spatial coverage. A critical assessment of the level of disagreement between expert coders further shows that there are few systematic predictors, providing no evidence for problematic biases among AFI coders. Overall, we conclude that the data quality of the AFI is comparatively high but that it could be further increased by recruiting even more experts and thereby enhancing the Bayesian IRT model’s performance. <br

Quality Assessment of the Academic Freedom Index: Strengths, Weaknesses, and How Best to Use It - Pelke, Lars; Spannagel, Janika (2023)
This paper reviews the data quality of the first systematic global measurement of academic freedom, namely the Academic Freedom Index (AFI) by using a data quality assessment approach proposed by McMann et al. (2022). By analyzing three distinct components of data quality (content validity, the data generation process, and convergent validity), this article examines the specific strengths and potential shortcomings of the AFI. The findings indicate that the AFI does well in terms of its theoretical embeddedness (within some conceptual limits), of the transparent data generation process and the handling of expert assessments, as well as of its temporal and spatial coverage. A critical assessment of the level of disagreement between expert coders further shows that there are few systematic predictors, providing no evidence for problematic biases among AFI coders. Overall, we conclude that the data quality of the AFI is comparatively high but that it could be further increased by recruiting even more experts and thereby enhancing the Bayesian IRT model’s performanc
Keywords: Academic Freedom Index; validity; reliability; academic freedom; Bayesian IRT

Reanalyzing the Link between Democracy and Economic Development - Pelke, Lars (International Area Studies Review, 2023)

Replikation als Lehrinstrument in der sozialwissenschaftlichen Methodenlehre. Der Praxiskurs Datenanalyse und Replikation. - Pelke, Lars (Heidelberg Inspirations for Innovative Teaching, 2022)
Der hier vorgestellte Praxiskurs Datenanalyse und Replikation setzt am Goldstandard wissenschaftlicher Forschung an und unterbreitet einen systematischen Ansatz Reproduktions- und Replikationsprojekte in die studentische Methodenausbildung zu integrieren. Die bisherige Methodenausbildung in der Politikwissenschaft setzt kaum auf den Lerngewinn, den Replikationsprojekte als Mittel des forschenden Lernens bieten können. Dieser Artikel argumentiert, dass politikwissenschaftliche Institute insgesamt gut beraten sind, Replikation entweder als Teil von Methodenkursen oder in Form von eigenen Replikationskursen in die studentische Methodenausbildung zu integrieren, um bereits bei Studierenden eine Kultur der Replikation und Reproduktion von Forschungsergebnissen zu verankern. Dieser Artikel arbeitet in einem ersten Schritt zunächst die Unterschiede zwischen Replikation und Reproduzierbarkeit heraus und stellt dann den Mehrwert dieser Projekte für den Lernprozess von Studierenden vor. Der Hauptteil stellt das hier entwickelte Lernprodukt vor und diskutiert die Planung und Durchführung ebenso wie die Anforderungen an Studierende und die Lernziele. Ferner sind die hier entwickelte Lernmaterialien und die Kurstruktur Open Access unter der Lizenz CC-BY-NC-SA lizensiert und können über GitHub abgerufen werden. Durch den hier vorgestellten Praxiskurs kann es gelingen, dass die Studierenden eine Replikationskultur für die eigene Forschung entwickeln, die dem Goldstandard von reproduzierbarer Forschung genügt.<br

Rethinking Inequality under Autocracy. Parties, Citizens, and Preferences - Pelke, Lars (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2021)
The causes of different levels of political and economic inequalities and related public policies under autocratic regimes are diverse. Existing works are mainly concerned with questions such as how political institutions matter for policy outcomes under authoritarianism and how citizens under autocratic rule adopt political and economic preferences conditioned by the nature of the regime environment. However, the literature still lacks a framework that systematically theorizes and empirically compares the effects of different institutional designs of dictatorships on policies that affect economic and political inequalities, such as redistribution and women's political inclusion. In addition, the consequences of political and economic inequality under authoritarianism for ordinary citizens are particularly important but are still understudied. The present dissertation seeks to answer whether and how the institutional foundations of autocracies determine economic and political inequalities and whether and how these inequalities affect ordinary citizens in the short and long term. The main argument at the heart of this dissertation is that autocratic institutions, and especially the strength of an incumbent's party, matter for redistributive policies and inequalities and their consequences for ordinary citizens. The four research papers that form the core of this dissertation employ quantitative methods with cross-national data on redistribution and women's political inclusion and individual-level data across countries on political participation and redistributive preferences. A crucial goal of this doctoral thesis is to propose a theoretical framework explaining public policies that address political and economic inequalities and the attitudinal effects of those policies and inequalities on ordinary citizens. The focus of my first dissertation paper is on theorizing and empirically examining variation in income redistribution across autocracies. It argues that the degree of electoral uncertainty affects two mechanisms that shape the redistributive nature of autocratic regimes. The inclusion and exclusion from political power on the grounds of socioeconomic and social attributes and the institutionalization of political parties determine autocrats' incentive and capacity for redistributing income and economic benefits. First, the empirical analysis suggests that more inclusionary ruling coalitions correspond with higher levels of income redistribution compared to more exclusionary regimes. Second, regimes with higher levels of party institutionalization redistribute more than regimes in which authoritarian parties are less institutionalized. However, third, the effects are largely conditional on electoral uncertainty. The second paper of this dissertation examines the association between women's political inclusion and incumbent party strength in authoritarian regimes and thereby investigates policies that autocratic regimes implemented to reduce this form of horizontal inequality. This article argues that the degree of party institutionalization is the main determinant of women's political inclusion under authoritarian rule. Similar to the first paper, it argues that institutionalized party rule determines authoritarian parties' incentive and capacity for introducing more gender-equal political processes and political outputs. Although previous research stressed the link between authoritarian regime types and gender equality, this study finds regime types explain little of the variation in gender equality. In contrast, regimes with higher levels of party institutionalization provide more gender-equal politics and policies than regimes in which authoritarian parties are less institutionalized. The third paper focuses on individuals living in autocratic regimes and their political participation. Thus, similar to the fourth paper, it shifts the level of inquiry to the individual level. The third paper investigates the following questions. What effect does economic inequality in authoritarian regimes have on the political participation of their citizens? Do individual income and repression each have a greater effect than economic inequality? The paper benefits from three prominent theories, namely the Conflict, Relative Power, and Resource Theories that address the inequality-participation puzzle in democracies. However, theoretical arguments and empirical evidence regarding non-democratic regimes are scarce. Thus, the third paper argues that it is individual income and the level of repression rather than economic inequality that explain political participation in autocracies. The paper demonstrates that higher levels of economic inequality hardly suppress political participation among citizens in general. However, individual income has a more powerful effect on civil society participation, while the level of repression decreases the likelihood of voting more strongly than income. The fourth paper sheds light on how authoritarian regimes have a lasting imprint on their citizens' ideas and values in the long term and on which mechanisms determine the redistributive preferences of their former citizens. It is widely established that autocracies attempt to indoctrinate their citizens to have compliant subjects. However, the long-term consequences of socialization under authoritarian rule are weakly conceptualized, and empirical evidence is rare, especially regarding citizens' economic preferences. The fourth paper proposes a distinction between three different mechanisms: state repression, political indoctrination, and exposure to autocracies during citizens' lifetimes. It finds that socialization under a highly indoctrinating regime leaves a strong pro-redistributive legacy, while highly repressive regimes also leave a pro-redistributive legacy. This study contributes to our understanding of how state repression and indoctrination affect ordinary citizens in the long term. This dissertation underlines the finding that highly institutionalized dictatorships provide public policies that address political and economic inequalities, while ordinary citizens are also affected by economic and political inequalities under autocratic rule. This doctoral thesis complements existing research on the causes and consequences of inequality under autocracy, socialization under authoritarianism, and citizens' preference formation in autocratic environments. <
Keywords: redistribution; authoritarian regimes; inequality; inclusionary regimes; party institutionalization; women’s equality; authoritarian regime types; women’s politics; economic inequality; political participation; voting; civil society; authoritarian legacies; state repression; indoctrination; ideologies; HAPC models; redistribution

So steht es um die Wissenschaftsfreiheit - Pelke, Lars; Kinzelbach, Katrin (2022)

Student-led replication studies in comparative politics: new findings by fresh eyes? - Korell, Daniel; Reinecke, Niklas; Lott, Lars (Zeitschrift für Vergleichende Politikwissenschaft, 2023)
This research note presents two replication studies that were conducted during a research-oriented course at Heidelberg University in summer 2022. The first study, initially conducted by Korell, replicates the findings from Albert’s original contribution on rebel governance. Albert conducted an explorative study in analyzing the associations between rebel governance and rebel military capacity. Our replication study indicates support for Albert’s argument of the relevance of disaggregating rebel governance, while we also show that the original findings are mainly driven by Albert’s explorative model specifications. The second study, initially conducted by Reinecke, tests the robustness of Levin et al.’s study on the democratic peacekeeping hypothesis and expands upon the original study by directly testing the “selectorate-theoretic causal mechanism” for the democratic peacekeeping hypothesis. Overall, the replication studies presented in this research note provide interesting findings regarding empirical conflict studies and contribute to ongoing efforts to promote replication initiatives in the education of future political scientists.<br
Keywords: Replication; Rebel governance; Democratic peacekeeping; Selectorate theory; Robustness test

The Ambivalent Effect of Autocratization on Domestic Terrorism - Lott, Lars; Croissant, Aurel; Trinn, Christoph (Studies in Conflict & Terrorism, 2023)
This study asks if a decline of democratic regime attributes affects the volume of domestic terrorism. We argue that different forms of autocratization may stimulate or suppress terrorist activities. Democratic backsliding may dampen domestic terrorism, while autocratic consolidation may make autocracies more vulnerable to terrorism. This study empirically tests these assumptions on time-series cross-sectional data on domestic terrorism in 182 countries between 1970 and 2020 with a difference-in-differences design. We find that democratic backsliding reduces the amount of terrorism in the short to medium term. Autocratic consolidation increases the number of terrorist attacks in the short to medium ter

Wie notwendig sind autonome Universitäten? Zum empirischen Zusammenhang der institutionellen und individuellen Wissenschaftsfreiheit - Kinzelbach, Katrin; Pelke, Lars (Forschung, Politik - Strategie - Management, 2022)

Wissenschaftsfreiheit unter der Lupe: Weltweiter Trend und Mobilität nach und aus Deutschland. In: Deutscher Akademischer Austauschdienst - Pelke, Lars; Spannagel, Janika; Kinzelbach, Katrin (2022)